Pembentukan Verba Transitif De Adjektiva Dalam Bahasa Minangkabau Dialek Kubung Tigo Baleh di Kenagarian Koto Gadang Guguak - Anggun Satriani; Ngusman Abdul Manaf (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
This study aims to describe the process of formation and meaning of transitive verb de adjectives in the Minangkabau language of the Kubung Tigo Baleh dialect in Kenagarian Koto Gadang Guguak, Solok Regency. This type of research is qualitative research using descriptive method. The data of this research are in the form of utterances that come from informants in the form of verb de adjectives in the Minangkabau language of the Kubung Tigo Baleh dialect in Kenagarian Koto Gadang Guguak. The data collection techniques used in this study were tapping techniques and fishing rods. Then the data analysis step is to transcribe the data from the recording into written form, identify the data according to the existing format, classify the data into verb formation and conclude the research results. The research findings show that the verb formation process is through the affixation process of transitive verb de adjectives in the Minangkabau language of the Kubung Tigo Baleh dialect in Kenagarian Koto Gadang Guguak. Then the meaning of the transitive verb de adjective consists of three, namely doing what is mentioned, in a state of making more.